Proceedings of the Fourth International Conference on Architectural Support for Programming Languages and Operating Systems - 1991
DOI: 10.1145/106972.106991
|View full text |Cite
|
Sign up to set email alerts
|

Limits of instruction-level parallelism

Abstract: The Western Research Laboratory (WRL) is a computer systems research group that was founded by Digital Equipment Corporation in 1982. Our focus is computer science research relevant to the design and application of high performance scientific computers. We test our ideas by designing, building, and using real systems. The systems we build are research prototypes; they are not intended to become products.There two other research laboratories located in Palo Alto, the Network Systems Laboratory (NSL) and the Sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
110
0
3

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 408 publications
(117 citation statements)
references
References 20 publications
4
110
0
3
Order By: Relevance
“…Until new technologies will emerge to address the power wall, the memory wall and the ILP wall [88, 177,181], CMPs are the architecture of choice in all fields of ICT. With CMPs becoming ubiquitous, parallel programming becomes a mandatory skill in order to fully exploit such architectures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Until new technologies will emerge to address the power wall, the memory wall and the ILP wall [88, 177,181], CMPs are the architecture of choice in all fields of ICT. With CMPs becoming ubiquitous, parallel programming becomes a mandatory skill in order to fully exploit such architectures.…”
Section: Discussionmentioning
confidence: 99%
“…Studies showed that high parallelism can only be extracted at very high hardware costs [177]. In the beginning of the 21st century common techniques for exploiting ILP became insufficient and it was said that single-core design has hit the ILP wall.…”
Section: The Ilp Wallmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the fact that confidence estimators [7,8] are able to assess the quality of conditional branch predictions, they have been adopted as building blocks in many applications [17][18][19][20][21]. Confidence estimators are very similar to branch predictors [22][23][24] in the sense that they have to make binary decisions (high-confidence and low-confidence or predicted-taken and predicted-untaken, respectively). Just like branch predictors, confidence estimators have a table of Miss Distance Counters (MDCs) to keep a historical record.…”
Section: Controlling Speculative Executionmentioning
confidence: 99%
“…We use two types of branch predictors [22,31]. One is a gshare branch predictor with 2048 entries and the other is a hybrid predictor that consists of the same gshare predictor and a 2048-entry bimodal predictor.…”
Section: Simulation Environmentmentioning
confidence: 99%